Human intracardiac SSEA4+CD34 cells show features of cycling, immature cardiomyocytes and are distinct from Side Population and C-kit+CD45- cells. - Mikael Sandstedt; Kristina Vukusic; Benjamin Ulfenborg; Marianne Jonsson; Lillemor Mattsson Hultén; Göran Dellgren; Anders Jeppsson; Jane Synnergren; Joakim Sandstedt (PLoS ONE, 2022)
Cardiomyocyte proliferation has emerged as the main source of new cardiomyocytes in the adult. Progenitor cell populations may on the other hand contribute to the renewal of other cell types, including endothelial and smooth muscle cells. The phenotypes of immature cell populations in the adult human heart have not been extensively explored. We therefore investigated whether SSEA4+CD34- cells might constitute immature cycling cardiomyocytes in the adult failing and non-failing human heart. The phenotypes of Side Population (SP) and C-kit+CD45- progenitor cells were also analyzed. Biopsies from the four heart chambers were obtained from patients with end-stage heart failure as well as organ donors without chronic heart failure. Freshly dissociated cells underwent flow cytometric analysis and sorting. SSEA4+CD34- cells expressed high levels of cardiomyocyte, stem cell and proliferation markers. This pattern resembles that of cycling, immature, cardiomyocytes, which may be important in endogenous cardiac regeneration. SSEA4+CD34- cells isolated from failing hearts tended to express lower levels of cardiomyocyte markers as well as higher levels of stem cell markers. C-kit+CD45- and SP CD45- cells expressed high levels of endothelial and stem cell markers-corresponding to endothelial progenitor cells involved in endothelial renewal.